2018
DOI: 10.1088/1361-648x/aadb6a
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-elastic switching of magnetostrictive nanomagnets with in-plane anisotropy: the effect of material defects

Abstract: We theoretically study the effect of a material defect (material void) on switching errors associated with magneto-elastic switching of magnetization in elliptical magnetostrictive nanomagnets having in-plane magnetic anisotropy. We find that the error probability increases significantly in the presence of the defect, indicating that magneto-elastic switching is particularly vulnerable to material imperfections. Curiously, there is a critical stress value that gives the lowest error probability in both defect-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The ∼ 10 −4 SAW-induced switching threshold for elliptical Ni nanomagnets appears to be significantly lower as compared to highly magnetostrictive thin films of Terfenol-D switchable by ultrashort longitudinal acoustic pulses with amplitudes ∼ 10 −2 propagating in the direction perpendicular to the surface [22]. This observation may seem surprising because of the ∼ 20 times larger magnetostriction coefficient in Terfenol-D [44]. However, the much longer ∼ 300 ps duration of the SAW pulses as compared to Ref.…”
Section: Switching Dynamics and Switching-time Diagramsmentioning
confidence: 87%
See 1 more Smart Citation
“…The ∼ 10 −4 SAW-induced switching threshold for elliptical Ni nanomagnets appears to be significantly lower as compared to highly magnetostrictive thin films of Terfenol-D switchable by ultrashort longitudinal acoustic pulses with amplitudes ∼ 10 −2 propagating in the direction perpendicular to the surface [22]. This observation may seem surprising because of the ∼ 20 times larger magnetostriction coefficient in Terfenol-D [44]. However, the much longer ∼ 300 ps duration of the SAW pulses as compared to Ref.…”
Section: Switching Dynamics and Switching-time Diagramsmentioning
confidence: 87%
“…The most critical assumption of the present study, i.e. the single-domain magnetic ground state of elliptic nanomagnets, depends on its dimensions and exchange stiffness [48,49] as well as the presence of nano-scale material defects [44]. Therefore, the experimental realization of the proposed SAW-induced magnetic recording will ultimately involve investigations of elliptical nanomagnets with different aspect ratios and dimensions.…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that the existence of possible structural defects like voids and impurities may hinder the strain‐induced magnetic switching. [ 53–55 ] For example, we found that after adding a cylindrical void with a diameter larger than 10nm to the upper magnetic layer, the bilayer system turns into a multidomain state with stripe domains upon application of a strain pulse ( ε xx , ε yy ) = (0.1%, −0.1%) (i.e., the condition for a parallel‐to‐antiparallel transition in a perfect sample), as shown in Figure . This would cause a failure of the strain‐induced transition.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed both experimentally [31,33] and theoretically [34,35] that strain, albeit energy-efficient, does not switch nanomagnets reliably, especially real nanomagnets that contain defects. This is the most serious drawback of magneto-elastic switching which is at the heart of straintronics.…”
Section: Non-boolean Straintronic Devices and Systemsmentioning
confidence: 99%